Faculty Conceptions of Teaching: Implications for teacher professional development - Varnava Marouchou, Despina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
In this paper, the need to assist university teachers in thinking carefully about what they are teaching, and how this relates to and coheres with their own professional development, is outlined. The underlying argument being made is that any efforts designed to extend and encourage scholarly teaching require us to consider the faculty experiences of understanding their subject matter, and in doing so, to help them to see how their understanding relates to what and how they teach. In other words exploring lecturers’ conceptions and epistemological beliefs about teaching may assist in the improvement of teacher education, professional development programs and teaching centres at the university.